Desain Charger Control Pembangkit Listrik Tenaga Hybrid Dengan Pengaturan Duty Cycle PWM - Leily W Johar (Universitas Batanghari Jambi, 2020)
The use of DC source voltage obtained from solar cells and DC generators varies in value depending on the surrounding natural conditions, for that a controller is needed which functions to regulate the voltage in carrying out the charging process to the accumulator. This paper will discuss about the design of charge controller based on Arduino Uno R3 with ATmega328 microcontroller. This controller is used to regulate the charging process from a DC source with a maximum open circuit voltage of 24 Volts, which is then used to charge the 12 Volt accumulator. This charge controller works by sending a source voltage that is regulated by pulse width modulation. When the accumulator voltage is 13.8 Volt, the controller will carry out a charging process with a duty cycle of 95%, if the accumulator voltage is> 13.8 Volts and ˂14.4 Volts, charging will be carried out with a duty cycle of 10%, and if the accumulator voltage exceeds 14.4 Volt, the charging process will be stopped. Some protection equipment is also included in this charge controller such as overvoltage protection, overcurrent and also control of the connection breaker to the load when the accumulator voltage is weak, and a disconnect from source to accumulator when the accumulator condition is full. To show the work of the whole system, with the Arduino Uno R3 microcontroller the parameters of source voltage, accumulator voltage and percentage of accumulator status are displayed on the LCD screen then 2 LED lights and a buzzer as indicators during the charging process and when the accumulator condition is weak. From the results of the voltage reading on the voltage divider sensor, it has an error of less than 6.22% at the source terminal and 6.89% at the accumulator terminal..